Modified Discontinuous Pulsewidth Modulation Approach With Independent Phase Loss Adjustment for Voltage Source Converters - Minh-Hoang Nguyen; Sangshin Kwak; Seungdeog Choi (IEEE Access, 2023)
This paper presents an efficient independent phase switching loss reduction technique for 2-level 3-phase voltage source inverters. A modified carrier-based pulse-width modulation algorithm, named per-phase discontinuous pulse-width modulation, is used to generate various non-switching intervals for the phase leg having the worst aging state by injecting a proper zero-sequence voltage to reference voltages. The non-switching intervals result in keeping a specific phase leg from switching to decrease the switching frequency and corresponding loss. The careful determination of variable clamping intervals aims to achieve a desirable decrease in the per-phase switching frequency of 2-level 3-phase voltage source inverters while ensuring that the output performance is not much degraded. The decrease in switching frequency and corresponding switching loss exerts a positive impact on the thermal stress of power semiconductor devices, resulting in improving the reliability of voltage source inverters. To evaluate the performance of the proposed method, the conventional carrier-based space vector modulation, 3-phase generalized discontinuous pulse-width modulation, and a discontinuous pulse-width modulation using hybrid offset voltage are implemented along with the proposed method. The accuracy and efficiency of the proposed method are validated using both simulation and experimental data.